WHY IS PULMONARY EMBOLISM STILL MISSED? CLINICAL PITFALLS, DIAGNOSTIC ERRORS AND CONTEMPORARY STRATEGIES FOR EARLY RECOGNITION - REVIEW - Mateusz Gadzina; Emilia Koziara; Julia Gawlak; Zofia Tarnawska; Karolina Figiel; Mateusz Gawin; Wojciech Sontag; Mateusz Zawisza; Aleksandra Golec; Maciej Krzesimir Kuswik (International Journal of Innovative Technologies in Social Science, 2026)
Pulmonary embolism (PE) remains a frequent, potentially fatal and persistently challenging diagnosis in emergency, inpatient and primary care settings. Although modern diagnostic pathways combine pre-test probability assessment, D-dimer testing and imaging, PE is still missed or diagnosed late because its presentation overlaps with pneumonia, chronic obstructive pulmonary disease exacerbation, acute coronary syndrome, heart failure, anxiety and other common conditions. This review synthesizes evidence on why PE continues to be under-recognized and how diagnostic pathways can be improved. The manuscript was developed on the basis of contemporary scientific literature, including clinical practice guidelines, clinical reviews, prospective studies, and studies evaluating diagnostic delay. The available evidence suggests that delayed recognition of pulmonary embolism is rarely caused solely by limited access to imaging studies. More often, it results from low initial clinical suspicion, atypical presentation, cognitive errors, inappropriate use of D-dimer testing, inconsistent application of clinical prediction rules, and limitations of imaging modalities.. Age-adjusted and clinical probability-adjusted D-dimer strategies, the YEARS algorithm and PEGeD approach reduce unnecessary imaging while maintaining diagnostic safety in selected patients. Future improvement depends on combining disciplined bedside reasoning with validated algorithms, targeted use of imaging, clinician education, and carefully evaluated artificial intelligence or electronic health record decision-support tools.